PERAN TEAM WORK DALAM UPAYA MENINGKATKAN KINERJAKARYAWAN PADA PT. ASURANSI SINARMAS CABANG MALANG - Riki Arizona (Faculty of Social and Political Science, 2017)
Duties and responsibilities in running a company, can not be left to just one person, in this case the leader. These duties and responsibilities must be borne by all people based on their expertise in their respective fields. Therefore, it takes a device called an organization. Organizations need integrated human resources. Human resource component of course has various expertise. For that, it takes a team work (teamwork) and work discipline that plays a role to run the organization. Teamwork in this study can also be called a working team. This teamwork is a way to work together. Teamwork is the one who runs all the management activities so that teamwork becomes the factors that affect the good and bad of the company's performance. Therefore, teamwork becomes an important element in the success of a company. Teams are better than individuals who act on their own or in larger organizational groups, especially when performance demands varying skills, judgments, and experiences. This study aims to describe the role of work team as one factor to improve employee performance in companies engaged in insurance. Insurance companies have their own peculiarities that make the author interested to do research. “PT Asuransi Sinarmas” is one of the largest insurance companies in Indonesia that has many variants of insurance products offered to its customers. In marketing insurance products required a solid and resilient work team. Where the performance of the company is realized from the quantity of insurance products that are in demand and required by its customers. The method used in this study using a qualitative research approach with the type of research in the form of case studies. The results of the study found that the role of team work is to determine the amount of target performance that has been determined by the leadership of the company.